Plant Density on Tidal Marsh Land Using Sentinel-2A NDVI Analysis Based on Land Drainability in Sri Mulyo Village, Indonesia - Mawardi, Abi Sahil; Sodik Imanudin, Momon; Jaya Priatna, Satria (Journal of Smart Agriculture and Environmental Technology, 2025)
Tidal marshlands have significant potential for agriculture, despite being affected by fluctuations in sea and river water. This study aims to analyze changes in vegetation density on agricultural land in Sri Mulyo Village, Air Saleh Sub-district, Banyuasin Regency, South Sumatra, using Sentinel-2A satellite imagery and the NDVI (Normalized Difference Vegetation Index) method. Observations were conducted in February, during the wet season, recorded a rainfall of 381 mm, while August, in the dry season, recorded a rainfall of 17 mm, based on data from the BMKG Climatology Station in Palembang for the year 2024, focusing on land cover changes in vegetation density under two different seasonal conditions. The analysis showed a decrease in the area with high vegetation density in August (56.01%) compared to February (63.97%), due to low rainfall and decreased soil moisture in the dry season. In contrast, the medium vegetation category increased in August. These findings suggest that seasonal variations significantly affect vegetation cover and productivity of tidal marshlands. as a consequence, during the dry season, increased drainability and reduced soil moisture contribute to a decline in  vegetation density, with the percentage of areas categorized as “High Greenness” decreasing to 56.01% and those categorized as “Moderate Greenness” increasing to 36.17%. These findings emphasize the crucial role of rainfall in sustaining vegetation in tidal marshlands, particularly under varying seasonal conditions.